(untitled) - Jack C Richards (New York, 1997)
The book is organized around high-interest topics that encourage students to talk about what they are most interested in: their own lives, aspirations, and interests. It activates both previous language knowledge and real-world experience, while presenting students with natural conversational language, idiomatic expressions, and communication skills.
Keywords: english language - listening english - problems, exercises, etc,english language - spoken english - problems, exercises, etc,english language - textbooks for foreign speakers